PENERAPAN PENDEKATAN SAINTIFIK PADA MATERI ORGAN GERAK HEWAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN 3 TEUPIN RAYA - Syarifah Rahmi; Nasri Diana (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2021)
This study aims to determine the increase in learning outcomes of fifth grade students at SDN 3 Teupin Raya on the material of animal extremities using a scientific approach. The method used is PTK. The population of this study was the fifth grade students of SDN 3 Teupin Raya in the second semester of the 2020/2021 academic year. The sample in this study consisted of 11 students consisting of 7 male students and 4 female students. The data was collected using lesson plans, LOAS, LOAG, and LKS in 3 cycles. In the first cycle the average value obtained was 67.72 with a percentage of 18.19%. In the second cycle the average value obtained by students was 74.54 with a percentage of 63 .6%. In the third cycle the average value obtained by students is 85.9 with a percentage of 100%. So it can be said that the increase in student learning outcomes obtained a value exceeding the predetermined KKM 75.